The Role and Urgency of Animation Media In The Development of Students' Cognitive Domain - Habibah, Fitriatul; Yori Marwinda; Septa Viani; Putri Ramadani (International Journal of Education and Teaching Zone, 2024)
The rapid development of technology has changed the goals of implementing the learning process. This research aims to determine the impact of animation media on students' cognitive learning outcomes in science learning. This type of research is descriptive qualitative. The population in the study was 16 students in class V of SD 113 Jambi City. The sample in this study used a total sampling technique, namely all Class V students totaling 16 students. The data collection technique uses test questions, then the test results will be analyzed by researchers to find out how much influence the students' cognitive domain has on the results of using animation media on student learning outcomes in science learning. The research results showed that the impact on students' cognitive domain was good at 62.5%, moderate at 31.25%, and 6.25% in the low category. The data obtained indicates that there is a good influence on learning outcomes in the cognitive domain of students.